Petrochemical Wastewater Treatment by Eggshell Modified Biochar as Adsorbent: Atechno-Economic and Sustainable Approach - Andy G. Kumi; Mona G. Ibrahim; Manabu Fujii; Mahmoud Nasr (Adsorption Science & Technology)
Petrochemical industrial wastewater (PIW)contains toluene and xylene (TX), and various organic and inorganic pollutants, causing severe risks to human health if improperly released into the environmental matrices. For the long-term reliability of environmental conservation, this study illustrates the interlinkage between PIW treatment and the three pillars of sustainable development. Sewage sludge biochar was modified with eggshell, showing a relatively high fixed C content (increase in carbonization degree), and small O/C and N/C ratios. The prepared biochar was employed for TX adsorption in mono-component solutions, giving removal efficiencies of 79.1% (T) and 86.6% (X), at pH =10, adsorbent dosage =2 g/L, and Co =40 mg/L within 60 min. The main adsorption mechanism was physisorption, including precipitation/pore-filling, π-π dispersive interaction, and van der Waals force. The modified biochar also treated real PIW under five adsorption/regeneration cycles, providing essential steps toward large-scale applications. According to an economic feasibility estimation, the biochar application for treating 1 m3 of PIW would offer a payback period of 6.9 yr. The study outputs could be linked to the restoration of water-related ecosystems, biochar modification for industrial applications, and climate change mitigation, adopting the 2030 agenda and its sustainable development goals (SDGs).